Contextual Effect of Community Health Center and Sosio-Demography Determinants on the Performance of Community Health Personnel in Karanganyar, Central Java - Mujiran Mujiran; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Community Health Center is a first-level health service facility that organizes public health efforts and individual health efforts. Good health service is supported by work performance of the health personnel. This study aimed to analyze the contextual effect of community health center and socio determinants on the work performance of health personnel.Subjects and Method: This was a cross sectional study conducted at Karanganyar community health centers, in Karanganyar, Central Java, from October to November 2019. A sample of 210 health workers was selected randomly. The dependent variable was work performance. The independent variables were age, education, tenure, distribution of services, work motivation, job skills, job satisfaction, health center accreditation status, and work environment. Data were collected by questionnaire and analyzed by a multilevel multiple logistic regression run on Stata 13.Results: Good work performance increased with age ≥38 years (b= 1.09; 95% CI= 0.19 to 1.99; p= 0.018), adequate service (b= 0.96; 95% CI= -0.28 to 2.19; p= 0.128), high motivation (b= 0.93; 95% CI= 0.09 to 1.77; p= 0.030), good job skills (b= 0.97; 95% CI= 0.06 to 1.88; p= 0.037), good job satisfaction (b= 0.92; 95% CI= 0.05 to 1.78; p= 0.037), and good working environment (b= 0.95; 95% CI= 0.11 to 1.80; p= 0.026). Good work performance decreased with education ≥Diploma III (b= -0.40; 95% CI= -1.67 to 0.87; p= 0.535) and tenure ≥3 years (b= -0.71; 95% CI= -1.79 to 0.37; p= 0.199). Community health center had strong contextual effect on work performance with ICC= 18.00%.Conclusion: Good work performance increases with age ≥38 years, adequate service, high motivation, good job skills, good job satisfaction, and good working environment. Good work performance decreases with education ≥Diploma III and tenure ≥3 years. Community health center has strong contextual effect on work performanceKeywords: work performance, health workers, contextual effect, multilevel analysisJournal of Health Policy and Management (2020), 05(03): 162-173https://doi.org/10.26911/thejhpm.2020.05.03.01